MODULO THEORY IN YAGER’S FERMATEAN FUZZY STRUCTURES - A.SHEELA ROSELIN; D.JAYALAKSHMI; *G.SUBBIAH (International Journal of Mathematical Archive, 2026)
In this article, we introduce the notion of a fermatean fuzzy sub-module. We prove various characteristics of fermatean fuzzy sub-module. We provide a relation between a fermatean fuzzy small module and a basic small module. Finally, some important properties regarding fermatean fuzzy small modules are investigated.